Genotyping-by-sequencing provides new genetic and taxonomic insights in the critical group of Centaurea tenorei - De Luca, Daniele; Del Guacchio, Emanuele; Cennamo, Paola; Paino, Luca; Caputo, Paolo (Frontiers in Plant Science, 2023)
Centaurea L. is one of the most widespread, differentiated, and critical genera of Asteraceae in the Euro-Mediterranean area, with more than 100 currently recognized species inhabiting the region. The controversial C. tenorei group, narrowly endemic to the Peninsula of Sorrento (Campania region, southern Italy), includes three weakly differentiated microspecies: C. tenorei Guss. ex Lacaita, C. montaltensis (Fiori) Peruzzi and C. lacaitae Peruzzi. However, their taxonomic distinctiveness and relationships with close or sympatric species are still unclear. In particular, the existence in several localities of individuals with intermediate morphology suggests inadequate taxonomic assessment within the group or hybridization and introgression with other species. In this study we aimed at defining population structure in this complex. With this objective, we sampled the three currently accepted species from their loci classici (i.e., the localities in which the taxa were originally described) and from other localities throughout the range, including populations of difficult identification occurring where the ranges of different taxa overlap. We employed a panel of SNPs obtained via genotyping-by-sequencing for investigations on genetic structure, admixture and ploidy inference, the latter also compared with chromosome counts. Our results showed that Centaurea tenorei s.l. is consistently tetraploid, contradicting the current taxonomy that was also based on ploidy level. Population structure analyses indicated the presence of four to seven clusters, most of which with clear evidence of admixture. Furthermore, contrarily to what previously supposed, we demonstrated a remarkable contribution of C. deusta, more that of C. cineraria in the genetic make-up of C. tenorei. However, we found a population of C. cineraria outside its ecological range, probably driven by climate change, which could be responsible in the future of further hybridization phenomena.